Effect of N and Zn Fertilization on the Uptake Pattern and Protein Content in T-aman Rice - Sarker, J. R.; Paul, A. K.; Paul, S. S. (International Journal of Bio-resource and Stress Management, 2010)
A field experiment was conducted at the research farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during T-aman season of 2006 on BRRI Dhan 39 to study the effect of N and Zn fertilization on N and protein content by T-aman rice. Four rates of each of nitrogen (N0=0, N1=50, N2=100 and N3=150 kg ha-1) and zinc (Zn0=0, Zn1=5, Zn2=10, and Zn3=15 kg ha-1) in all possible combinations were applied following a randomized block design with three replications. Application of N and Zn fertilizers caused an increase in concentration of N and protein in rice grain with increasing level of the fertilizers over the control. However, N and Zn fertilizers showed a positive and significant effect on N and protein content of rice grain irrespective to the treatments applied. It is evident that nitrogen and protein content in rice grain increased with increasing level of N upto certain level. The highest N and protein content in rice grain and straw was found due to application of N at higher level (150 kg ha-1). On the other hand, the highest N and protein content in rice grain and straw was observed in Zn3 treatment. N and Zn uptake by rice grain significantly increased with increasing level of N upto 100 kg ha-1 and then decreased. However, the highest N uptake by straw was observed in N3, N2 treatment and Zn3, Zn2 treatment, respectively. The highest N and protein content in rice grain was recorded in N3Zn2 treatment. The treatment combination of N and Zn showed no significant variation in Zn content of rice grain. However, the highest uptake of N and Zn was observed in N2Zn2 and N2Zn3 treatment combinations.